Viral symptoms in children and SARS-COV-2: information for pediatric dentists for the control of transmission - Thaysa Gomes Ferreira Tenório dos Santos; Débora Heloísa Silva de Brito; Natália Maria Velozo dos Santos; Mabel Cristina Paiva; Maria Carlla Aroucha Lyra; Mônica Vilela Heimer; Arnaldo de França Caldas Júnior; Aronita Rosenblatt (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract: The new coronavi rus, which has spread worldwide, has spiraled out of control in Brazil. The number of infected children has increased, and more Infants Special Care Units are needed to prevent deaths. This study aims to report the most common signs and symptoms in children infected by seasonal respiratory viruses and those infected by COVID-19. This knowledge is essential to educate pediatric dentists, who may contribute to identifying the difference in symptoms and notify the cases, thus preventing the spread of COVID-19. This study was carried out in a Family Health Center of Ipojuca, state of Pernambuco, Brazil, and included 54 children seen for dental emergency care. The parents provided information about the signs and symptoms of their children' s health conditions during the lockdown from March to July 2020. All children had a serological test to detect any exposure to the virus. Kolmogorov-Smirnov and Mann-Whitney tests were used to assess the distribution of the data and compare the quantitative variables between the groups. Among the study participants, 16.7% tested positive for COVID-19. The most prevalent symptoms were headache (38.9%), sneezing (35.2%), and fever (20.4%); six out of nine children with a positive test had symptoms after infection of an adult in the family. Children infected with COVID-19 showed similar clinical signs to those with negative results. Pediatric dentists should acquire knowledge to report on sick children and prevent the spread of the disease.